ISLAM LIBERAL DI INDONESIA (PEMIKIRAN DAN PENGARUHNYA DALAM PEMIKIRAN POLITIK ISLAM DI INDONESIA - Erowati Dewi (Program Studi Sarjana (S1) Ilmu Pemerintahan, FISIP, Universitas Diponegoro, 2016)
This article is an author’s analysys of Liberal Islamic Thought and its influence on Islamic politics in Indonesian. The issues in this paper are: (a) What is Liberal Islam and Liberal Islam typology?, (b) What is the thought of Liberal Islam in Indonesia?, (c) How is the influence of Liberal Islamic thought in Indonesia? The Liberal Islamic Thoughts described in this article include opposing the idea of an Islamic state (secular), pluralism, democracy, and gender equality having an influence on Islamic political thought. The influence is gaining resistance from fundamentalists, where fundamentalist thinking is to want an Islamic state.